The Spatial Organization of the VirR Boxes Is Critical for VirR-Mediated Expression of the Perfringolysin O Gene, pfoA, from Clostridium perfringens - Cheung, Jackie K. (American Society for Microbiology, 2004)
The transcriptional regulation of toxin production in the gram-positive anaerobe Clostridium perfringens involves a two-component signal transduction system that comprises the VirS sensor histidine kinase and its cognate response regulator, VirR. Previous studies showed that VirR binds independently to a pair of imperfect direct repeats, now designated VirR box 1 and VirR box 2, located immediately upstream of the promoter of the pfoA gene, which encodes the cholesterol-dependent cytolysin, perfringolysin O. For this study, we introduced mutated VirR boxes into a C. perfringens pfoA mutant and found that both VirR boxes are essential for transcriptional activation. Furthermore, the spacing between the VirR boxes and the distance between the VirR boxes and the −35 region are shown to be critical for perfringolysin O production. Other VirR boxes that were previously identified from the strain 13 genome sequence were also analyzed, with perfringolysin O production used as a reporter system. The results showed that placement of the different VirR boxes at the same position upstream of the pfoA promoter yields different levels of perfringolysin O activity. In all of these constructs, VirR was still capable of binding to the target DNA, indicating that DNA binding alone is not sufficient for transcriptional activation. Finally, we show that the C. perfringens RNA polymerase binds more efficiently to the pfoA promoter in the presence of VirR, indicating that interactions must occur between these proteins. We propose that these interactions are required for VirR-mediated transcriptional activation.